From Sounds to Meaning: A Case Study of Linguistic Development in a Preschool-Age Indonesian Child (Sastra Inggris UNPAM, 2025)
This study investigates the phonological, morphological, and semantic aspects of spontaneous speech in a four-year-old child, aiming to uncover developmental patterns and common linguistic challenges during early language acquisition. Employing a qualitative case study approach, naturalistic data were collected through audio and video recordings of the child's daily conversations. The transcribed speech was analyzed to examine articulation, word formation, and meaning construction. The findings revealed systematic phonological processes such as consonant substitution (/r/ to /l/), simplification of consonant clusters, and omission of final consonants. Morphological observations included frequent use of reduplication and overgeneralized application of the derivational suffix -in. Semantically, the child demonstrated an emerging lexicon with early signs of conceptual confusion and limited categorical differentiation. These developmental characteristics suggest that while the child is actively internalizing language rules, the acquisition process remains error-prone and exploratory. The study highlights the importance of meaningful interaction, corrective input, and exposure to rich linguistic environments in supporting children’s language growth. The insights gained are relevant for parents, educators, and speech-language practitioners in designing age-appropriate strategies that nurture early communicative competence.